Ecotourism - Center for Natural Resources (EDIS)
Though the concept of nature-based tourism is not new, the term "ecotourism" is. Once referred to as "green travel", ecotourism is defined as a "recreational and educational experience that encourages greater understanding of the natural and cultural resources of an area". This publication was produced by the Center for Natural Resources at the University of Florida. CNR 7 is part of a Program Summary Series. First published: September 2000. Minor revision: March 2003.